Sustainable tourism planning and climate change adaptation in the Alps: a case study of winter tourism in mountain communities in the Dolomites. Issue 4 (2nd April 2016) - Bonzanigo, Laura; Giupponi, Carlo; Balbi, Stefano
ABSTRACT: A vast body of literature suggests that the European Alpine Region is extremely sensitive to climate change. Winter tourism is closely related to climate variations, especially in mountain regions where resorts are heavily dependent on snow. This paper explores how to effectively integrate a climate change adaptation perspective with local discourses about sustainability and tourism, an increasing priority for policy-makers in the region and elsewhere. It reports on the development and application of a participatory decision support process for the analysis of adaptation strategies for local development of an Alpine tourism destination, Auronzo di Cadore (Dolomites, Italy). This experience significantly contributed to the idea that an efficient combination of modelling capabilities, decision support tools, and participatory processes can substantially improve decision-making for sustainability. The authors show that, in this case study, such a combination of methods and tools allowed for managing the involvement of local actors, stimulating local debates on climate change adaptation and possible consequences on winter tourism, encouraging creativity and smoothing potential conflicts, and easing the integration of the qualitative knowledge and the preferences of the involved actors with quantitative information. This contributed to an integrated sustainability assessment of alternative strategies for sustainable tourism planning.